BENARKAH NABI MUHAMMAD SIX PACK? (STUDI TAKHRIJ HADIS) - Hartono, Sidiq; Sulidar; Zulkarnaen (Qolamuna : Jurnal Studi Islam, 2024)
This research was conducted due to the spread of a misconception claiming that Prophet Muhammad (peace be upon him) had a Sixpack abdomen, and that having a Sixpack is a Sunnah of the Prophet, both on websites and social media platforms. This is concerning as it is highly dangerous to attribute something unverifiable to the Prophet by relying on it. The #abschallenge trend has contributed to spreading this hadith, especially among Muslims who are enthusiastic about sports. A health perspective is also incorporated in this research to provide a comparison with science. This qualitative study utilizes a literature review with the application of the takhrij al-hadith method, and the interpretation in the discussion employs content analysis. The results indicate that there is no strong and convincing hadith confirming that Prophet Muhammad (peace be upon him) had a Sixpack abdomen, thus the understanding that having a Sixpack is a Sunnah is erroneous. When correlating the lifestyle of Prophet Muhammad (peace be upon him) with the Sixpack theory, it is found that it is possible that Prophet Muhammad (peace be upon him) had a Sixpack abdomen. Keywords : Sixpack; Hadith; Sunnah; Prophet Muhammad.